Influencia de las redes sociales en la educomunicación de los jóvenes de la parroquia 24 de mayo de la ciudad de Quevedo, año 2021 - Olvera Chevez, Lady Lisseth (2021)
Educommunication was initially related to popular education, but today it is understood as a behavior that addresses the digital transformation in a world of screens, which educate humanity. The challenges are enormous, due to the existence of a great analog gap between the connected and the non-connected and due to the overload of information that is manipulated through the media. It is necessary to emphasize that distance education processes imply a teacher-student relationship that is very different from the face-to-face one, hence the importance of knowing and understanding the argument of this type of education that generates stress and fatigue on both sides. It is intended to know what happens to the other side of the screen, which is why the teacher must be able to attend and know his virtual students and one of the links between teaching and communicating that begins at the end of Educommunication. Currently, social networks have gained strength in the education and communication of young people, it is for this reason that it was proposed as a research topic "Influence of social networks in the Educommunication of young people of the Parish May 24 of the city de Quevedo” to understand how this problem is triggered. Social networks provide a lot of information to teachers, students and their families, so it is important to understand how this issue develops, from critical thinking, which can be approached from Educommunication.